Spatial impact effects of coupled coordination between forestry factor endowment and technological progress bias on forestry industry structural upgrading in China - Jiang, Yu; Liao, Yuanwei; Shen, Canyu (Frontiers in Environmental Science, 2024)
IntroductionThe biased technological progress coordinated with factor endowment is an important support for achieving sustainable development in the forestry industry. This study focused on the coupled coordination relationship between forestry factor endowment and technological progress bias, analyzing their spatial impacts on the upgrading of forestry industry structure. The aim is to fully leverage the driving force of technological progress to promote sustainable development of the forestry economy.MethodsCovering the years from 2005 to 2021, this study calculated the coupling coordination and constructed spatial econometric models to empirically analyze its spatial impacts on the rationalization, advancement, and ecologicalization of the forestry industry structure.Results and DiscussionThe results indicated that the overall level of coupling coordination was relatively low, with certain differences among provinces. The upgrading of the forestry industry structure showed significant spatial correlation, and after considering the cumulative effects of industrial structure upgrading, there existed a positive spatial spillover effect among regions. The improvement of coupling coordination promoted the rationalization and ecologicalization of industrial structure. However, in the short term, it had a negative impact on advancement. For the four major regions, the low level of coupling coordination and regional differences remained key obstacles hindering the promotion of industrial structure upgrading through technological progress. Therefore, there is a need to further optimize the coupling coordination between factor endowment and technological progress bias and place greater emphasis on regional coordinated development. This study may provide new insights into the development of the forestry industry from the perspective of the coupling of factors and technology, emphasizing the necessity of coupling forestry resource endowment with technological progress.